2023
DOI: 10.15403/jgld-4508
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of Treatment Options for the Prevention of Post-TIPS Hepatic Encephalopathy: A Systematic Review and Network Meta-analysis

Abstract: Background and Aims: Transjugular intrahepatic portosystemic shunt (TIPS) is often used in patients with cirrhosis to manage portal hypertension-related complications. Unfortunately, 35-50% of patients develop overt hepatic encephalopathy (HE) after TIPS. However, data on lactulose and rifaximin to prevent post-TIPS HE is limited. Therefore, we aimed to perform a network meta-analysis to investigate the efficacy of multiple pharmacological regimens in the prevention of post-TIPS HE. Methods: A comprehens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Reviews and meta-analyses have scrutinised the data from the treatment studies. The two most recent studies found that neither lactulose alone, rifaximin alone, nor a combination of both significantly reduced the incidence of post-TIPS HE [ 122 , 123 ]. Furthermore, they emphasize that the evidence is scarce, and more studies on combination therapy are needed.…”
Section: He Prophylaxismentioning
confidence: 99%
“…Reviews and meta-analyses have scrutinised the data from the treatment studies. The two most recent studies found that neither lactulose alone, rifaximin alone, nor a combination of both significantly reduced the incidence of post-TIPS HE [ 122 , 123 ]. Furthermore, they emphasize that the evidence is scarce, and more studies on combination therapy are needed.…”
Section: He Prophylaxismentioning
confidence: 99%